2014
DOI: 10.1021/jf500159z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antiproliferative Activity Constituents from Artocarpus heterophyllus

Abstract: Artocarpus heterophyllus is an evergreen fruit tree cultivated in many tropical regions. Previous studies have shown that some of its compositions exhibited potential tyrosinase inhibition activities. This study indentified 8 new phenolic compounds, artoheterophyllins E-J (1-6), 4-geranyl-2',3,4',5-tetrahydroxy-cis-stilbene (7), and 5-methoxymorican M (8) and 2 new natural compounds (9 and 10), 2,3-dihydro-5,7-dihydroxy-2-(2-hydroxy-4-methoxyphenyl)-4H-benzopyran-4-one and 6-[(1S,2S)-1,2-dihydroxy-3-methylbuty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…The IR and UV data indicated that 2 possessed flavanone skeleton. The 1 H-NMR spectrum of 2 was very similar to that of the known compound 3, [2] and a comparison of those of 2 and 3 showed the signals of the following protons: an aromatic ABX spin system at δ 7. C NMR spectrum of 2, the chemical shift values of all the carbon atoms except that of C-6 were similar to those of the relevant carbon atoms of 3.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…The IR and UV data indicated that 2 possessed flavanone skeleton. The 1 H-NMR spectrum of 2 was very similar to that of the known compound 3, [2] and a comparison of those of 2 and 3 showed the signals of the following protons: an aromatic ABX spin system at δ 7. C NMR spectrum of 2, the chemical shift values of all the carbon atoms except that of C-6 were similar to those of the relevant carbon atoms of 3.…”
Section: Resultsmentioning
confidence: 59%
“…[2,6] The anti-respiratory burst activities of the four isolated compounds 1-4 were biologically evaluated by determining luminol-dependent chemiluminescence in rat PMNs. All of these compounds exhibited significantly suppressive activity on respiratory burst of rat PMNs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Previous phytochemical research on plants of this genus led to diverse prenylated flavonoids and stilbenoids with interesting biological activities such as cytotoxic, [5][6][7][8][9][10] antiinflammatory, [11][12][13][14][15] antioxidant, 16,17) antimalarial, 18,19) and antifungal activities, 20) as well as tyrosinase inhibitory activities 21,22) and 5α-reductase inhibitory activities. 23) As part of our ongoing efforts to discover novel potential anticancer leads from Moraceous plants, 24) two new prenylated flavones (2, 12) along with 13 known compounds (1, 3-11, 13-15) have been isolated from the twigs of Artocarpus nigrifolius C. Y. WU for the first time.…”
mentioning
confidence: 99%
“…Recently, extracts isolated from Artocarpus heterophyllus (jackfruit) reported to show anti-proliferative properties on human cancer cell lines and murine B-cell lymphoma (11,12). ArtinM is a d-mannose-binding lectin found in the seeds of Artocarpus heterophyllus that interacts with N-glycans and is associated with receptors on the surface of phagocytic cells to induce production of inflammatory mediators, such as tumor necrosis factor alpha (TNFα) (13), interleukin 12 (IL12) and interferon gamma (IFNγ) (14).…”
mentioning
confidence: 99%